Foreign language vocabulary learning and the type of processing-resource allocation model - Shusaku Kida (Vocabulary Learning and Instruction)
This paper argues the nature of adult foreign or second language (L2) vocabulary learning and points out the importance of word-form learning at the initial stage of vocabulary development. The Type of Processing-Resource Allocation (TOPRA) model is introduced as a prominent theoretical framework to capture it. Finally, some future studies are proposed to reinforce TOPRA-based studies with respect to (1) types of vocabulary processing tasks and (2) dimensions of vocabulary development.